Structure of a Moloney murine leukemia virus-virus-like 30 recombinant: implications for transduction of the c-Ha-ras proto-oncogene. - Makris, A (1993)
Tumor progression locus 2 (Tpl-2) encodes a novel serine-threonine protein kinase which is activated by provirus integration in the late stages of oncogenesis in Moloney leukemia virus (MoMuLV) induced rat T-cell lymphomas. In this report, we present evidence that the provirus integrated in the Tpl-2 locus in 1 of 10 T-cell lymphomas harboring a Tpl-2 rearrangement (2779) is a recombinant between MoMuLV and virus-like 30 (VL30) sequences (Mo-VL30). Recombination between MoMuLV and VL30 may contribute to the transduction of ras, as suggested by the finding that VL30 flanks the ras oncogene in all of the ras transducing viruses isolated from rats to date. The Mo-VL30 recombinant described here represents evidence that recombination between MoMuLV and VL30 can be uncoupled from the transduction of ras, and it may precede the transduction. Sequence comparison between clones of Mo-VL30, Harvey sarcoma virus (Ha-MSV), and genomic c-Ha-ras revealed that all three share a 124-bp region of 87.3% homology. This region was detected at nucleotide positions -1845 to -1720 of c-Ha-ras and 20 bp 5' of the recombination breakpoint between VL30 and ras in Ha-MSV. On the basis of the sequence comparison between VL30, Ha-MSV, and c-Ha-ras, we are proposing a model which explains how VL30 may have facilitated the transduction of c-Ha-ras and perhaps the other ras proto-oncogenes. According to this model, the sequence homology between VL30 and c-Ha-ras targets this gene for transduction by promoting the integration of the provirus in this locus through homologous recombination.